Correlation of Serum Ferritin with Age and Growth in Thalassemia Major Children (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Thalassemia is the most prevalent single gene defect in human beings worldwide. Repeated blood transfusions along with chelation therapy are mainstay of treatment in thalassemia patients. However, these recurrent blood transfusions along with inadequate chelation therapy results in iron overload. The study aimed to investigate the serum ferritin level in children with blood transfusion in thalassemia major patients and to know their correlation with age and growth. Materials and methods: A cross-sectional analytical study was conducted including 79 children of thalassemia major in the age group of 5-12 years who were on regular blood transfusion and oral iron chelators from thalassemia unit of Chittagong Medical College Hospital. Serum ferritin was tested and their correlation with age and growth was assessed. Chi square was done to determine the correlation. Results: The age of the patients ranged from 5 to 12 years and 45(56.9%) were males. The mean age at diagnosis of thalassemia was 10.7±4.2 months and mean number of transfusion was 90±29 and ranged between 40-140 transfusions. All of the children were on oral iron chelation therapy and the average age of initiation chelation therapy was 5.7±1.1 years. 64(81%) children had growth retardation. Mean serum ferritin level was 3740.7±2185.8 ng/ml and only 3.8% of the patients had serum ferritin level